Manajemen Pembinaan Kinerja Guru Raudlatul Athfal (RA) dalam Bentuk Balanced Scorecards (BSC) - Fu'ad Arif Noor (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
A management capability that can be adopted in nonprofit organizations, a performance appraisal tool called the Balanced Scorecard (BSC) is a performance appraisal method. This method assessed the performance of a set of performance measures that have been compiled based on. The BSC bases its performance appraisal in four important perspectives: financial perspective, customer perspective, internal process perspective, and learning and growth perspective. The performance of RA Teachers is its success in providing efforts to stimulate, guide, nurture and provide learning activities that will result in skills and skills in child planning, implementing and evaluating teaching and learning processes that are based on the mental attitude and professionalism of teachers. The essence of teacher performance is none other than the ability of teachers to demonstrate the skills or competencies they have in the real world of work. The real world of teacher work is to teach children or their students in classroom learning activities, in performance based on pedagogical competence, personality competence, social competence, professional competence, and leadership.